2014
DOI: 10.1097/ccm.0b013e3182a275b1
|View full text |Cite
|
Sign up to set email alerts
|

Are Autopsy Findings Still Relevant to the Management of Critically Ill Patients in the Modern Era?

Abstract: We detected a lower rate of clinicopathological discrepancy in critically ill patients than previously reported. Potential reasons for such findings include advances in diagnostic techniques and the use of a more robust definition to classify diagnostic discrepancies. Autopsy can still identify discrepancies in diagnosis even in patients who have undergone appropriate investigations. Prospective research is required to accurately define discrepancy rates in the critically ill population and to identify the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
1
14
2
5
Order By: Relevance
“…In the ICU setting, autopsy studies [1315] have been performed to assess the discrepancies between clinical and post-mortem diagnoses. Nevertheless, there is scant information in the literature on the rates of autopsy performed to identify the etiology of lethal shock.…”
Section: Discussionmentioning
confidence: 99%
“…In the ICU setting, autopsy studies [1315] have been performed to assess the discrepancies between clinical and post-mortem diagnoses. Nevertheless, there is scant information in the literature on the rates of autopsy performed to identify the etiology of lethal shock.…”
Section: Discussionmentioning
confidence: 99%
“…Flera studier under 2010-talet visar att obduktion är ett viktigt verktyg för att upptäcka diagnostiska misstag (Liao & Singh, 2013;Scordi-Bello et al, 2010;Tejerina et al, 2012). Genom att jämföra kliniska diagnoser med obduktionsprotokoll har man i studier visat (Alafuzoff & Veress, 1993;Fröhlich et al, 2014) att obduktionen till ca 75% kommer med tillägg som har betydelse för dödsfallet och påverkar dödsorsaksintyget. I studier på intensivvårdsavdelningar kan man i två studier (Fröhlich et al, 2014;Wong et al, 2015) se en lägre diskrepans mellan klinisk diagnos och diagnos efter obduktion.…”
Section: Diagnos Före Och Efter Obduktionunclassified
“…Genom att jämföra kliniska diagnoser med obduktionsprotokoll har man i studier visat (Alafuzoff & Veress, 1993;Fröhlich et al, 2014) att obduktionen till ca 75% kommer med tillägg som har betydelse för dödsfallet och påverkar dödsorsaksintyget. I studier på intensivvårdsavdelningar kan man i två studier (Fröhlich et al, 2014;Wong et al, 2015) se en lägre diskrepans mellan klinisk diagnos och diagnos efter obduktion. Fröhlich et al fann i sin studie att flera patienter inom intensivvården obducerades av rättsmedicinsk anledning.…”
Section: Diagnos Före Och Efter Obduktionunclassified
See 1 more Smart Citation
“…The landmark study by Goldman et al 1 found a 10% error rate in diagnosis in 100 randomly chosen autopsies. Their original classification of diagnostic errors was modified by Frohlich et al 2 in 2014 (Table 1). More recent analysis quotes a discrepancy rate of between 20% and 44% 3 despite improvements in modern imaging and diagnostic processes.…”
Section: Getting Death Right and Improving Practicementioning
confidence: 99%